Pengaruh Penyajian Laporan Keuangan, Aksesibilitas, dan Pengawasan Kualitas Laporan Keuangan terhadap Akuntabilitas Pengelolaan Keuangan Daerah : (Studi Pada DPRD Kota Surakarta) - Asep Nanda Paramayana; Riana Rachmawati Dewi; Agni Astungkara (Politeknik Ganesha Medan, 2022)
Government financial statements are intended to provide information useful for decision-making and represent the reporting entity's responsibility for entrusted resources. While financial reporting is required, access to and monitoring of financial reporting quality to enhance accountability in regional financial management. The purpose of this study was to determine the effect of the presentation of financial statements, accessibility, and supervision on the accountability of regional financial management of the Surakarta City DPRD. This research is quantitative. The population consists of 44 employee of the Surakarta City DPRD. The number of samples is 44 employee of the Surakarta City DPRD. The data analysis technique used multiple linear regression analysis. This research is indicated by the results of the presentation of financial statements that affect the accountability of regional financial management to the Surakarta City DPRD. Accessibility affects the accountability of regional financial management to the Surakarta City DPRD. Supervision of the quality of financial reports affects the accountability of regional financial management to the Surakarta City DPRD. The sample is only 44 employee of the Surakarta City DPRD. If the number of samples is increased, better results are likely to be obtained. The next researcher, can add the number of samples of other research objects.